Pharmacokinetic drug–drug interaction study of ranolazine and metformin in subjects with type 2 diabetes mellitus. Issue 2 (22nd January 2015) - Zack, Julia; Berg, Jolene; Juan, Axel; Pannacciulli, Nicola; Allard, Martine; Gottwald, Mildred; Zhang, Heather; Shao, Yongwu; Ben‐Yehuda, Ori; Jochelson, Phil
Abstract Ranolazine and metformin may be frequently co‐administered in subjects with chronic angina and co‐morbid type 2 diabetes mellitus (T2DM). The potential for a drug–drug interaction was explored in two phase 1 clinical studies in subjects with T2DM to evaluate the pharmacokinetics and safety of metformin 1000 mg BID when administered with ranolazine 1000 mg BID (Study 1, N = 28) or ranolazine 500 mg BID (Study 2, N = 25) as compared to metformin alone. Co‐administration of ranolazine 1000 mg BID with metformin 1000 mg BID resulted in 1.53‐ and 1.79‐fold increases in steady‐state metformin Cmax and AUCtau, respectively; co‐administration of ranolazine 500 mg BID with metformin 1000 mg BID resulted in 1.22‐ and 1.37‐fold increases in steady‐state metformin Cmax and AUCtau, respectively. Co‐administration of ranolazine and metformin was well tolerated in these T2DM subjects, with no serious adverse events or drug‐related adverse events leading to discontinuation. The most common adverse events were nausea, diarrhea, and dizziness. These findings are consistent with a dose‐related interaction between ranolazine and metformin, and suggest that a dose adjustment of metformin may not be required with ranolazine 500 mg BID; whereas, the metformin dose should not exceed 1700 mg of total daily dose when using ranolazine 1000 mg BID.